2002
DOI: 10.1007/s101620020044
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anesthesia on Efferent-Mediated Adaptation of the DPOAE

Abstract: Distortion product otoacoustic emissions (DPOAE) adapt after primary tone onset, with an approximately 100 ms time constant, due to feedback effects of medial olivocochlear (MOC) activity elicited by the primary tones. We tracked DPOAE postonset adaptation as a metric of MOC reflex strength, before during and after induction of anesthesia in guinea pigs. Reflex strength was significantly diminished by the barbiturate/neuroleptic anesthesia most commonly used in this species. The MOC reflex recovered more slowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 23 publications
(37 reference statements)
4
42
0
Order By: Relevance
“…The large amplitudes of the DPOAE changes we observed indicate that the combination of urethane/fentanyl anesthesia produced preinjection reflex strengths approximately as large as those seen in awake animals (Boyev et al, 2002), thus this anesthetic regimen apparently does not significantly diminish the MOC reflex.…”
Section: Dpoae Post-onset Effects As a Moc Reflex Metricmentioning
confidence: 58%
See 2 more Smart Citations
“…The large amplitudes of the DPOAE changes we observed indicate that the combination of urethane/fentanyl anesthesia produced preinjection reflex strengths approximately as large as those seen in awake animals (Boyev et al, 2002), thus this anesthetic regimen apparently does not significantly diminish the MOC reflex.…”
Section: Dpoae Post-onset Effects As a Moc Reflex Metricmentioning
confidence: 58%
“…Test/retest measurements (see Materials and Methods section) suggested that the Ipsi reflex metric varied as much as 29% and the smaller Contra metric varied as much as 45%. Changes in metrics greater than these values will be thus be considered significant.The large amplitudes of the DPOAE changes we observed indicate that the combination of urethane/fentanyl anesthesia produced preinjection reflex strengths approximately as large as those seen in awake animals (Boyev et al, 2002), thus this anesthetic regimen apparently does not significantly diminish the MOC reflex. …”
mentioning
confidence: 58%
See 1 more Smart Citation
“…In the first study (Young and Barta 1986), responses to tones in background noise were measured for cats anesthetized with sodium pentobarbital. The dose of the anesthetic was adjusted to maintain the animals in an areflexive state, so the MOCR was greatly reduced in these animals (Boyev et al 2002). Tone bursts with a duration of 200 ms were presented at the AN fiber's characteristic frequency (CF), in quiet and in three levels of background noise.…”
Section: Comparing Physiological and Modeling Estimates Of Mocr Gain mentioning
confidence: 99%
“…Furthermore, broadband noise typically evoked higher MOC firing rates than tones (Liberman 1988;Brown et al 1998), which is consistent with the MOC neurons integrating afferent activity broadly across frequency. Another factor is that all of the recordings from single MOC fibers were from anesthetized animals but MOC activation is stronger in awake animals (Boyev et al 2002). Overall, it seems likely that (1) the narrow tone TCs from MOC fibers are not good indicators of brainstem across-frequency convergence of MOC activation, (2) both humans and animals have MOC systems that integrate incoming activation widely across cochlear regions, and (3) the frequency integration of MOC effects in awake humans shown by both Figs.…”
Section: How Does the Observed Inhibition Of Sfoaes Correspond To Neumentioning
confidence: 99%